(untitled) - Hiller, Johann Adam (Cambridge,New York, 2001)
Hiller's Treatise on Vocal Performance and Ornamentation was published in Germany in 1780 and is an important manual on vocal technique and performance in the eighteenth century. Hiller was a masterful educator and was active not only as a teacher but as a critic, composer, conductor and music director. Thus, his observations served not only to raise the standards of singing in Germany, based on the Italian model, but to present complicated material, particularly ornamentation, in a manner that his peers, the middle class could emulate. This present edition, translated with an introduction and extensive commentary by musicologist Suzanne J. Beicken, makes Hiller's treatise available for the first time in English. With its emphasis on practical aspects of ornamentation, declamation and style it will be valuable to instrumentalists as well as singers and is a significant contribution to the understanding of performance practice in the eighteenth century.
Keywords: Singing,Embellishment (Music),Tiếng hát,Sự làm đẹp